Identifikasi Bangun Ruang yang terdapat pada Batu Kubur Kampung Waitabar Kecamatan Loli Kabupaten Sumba Barat - Marawali, Robinson; Wole, Kristoforus Daka; Lede, Yulius Keremata (Indo-MathEdu Intellectuals Journal, 2025)
Ethnomathematics is a science used to understand how mathematics is adapted from a culture and serves to express the relationship between culture and mathematics. This study aims to explore ethnomathematics on gravestones in Waitabar Village, Loli District, West Sumba Regency. This research is a qualitative study with an ethnographic approach. The research subjects are people, places, or objects observed as targets. The subjects in this study were gravestones in Waitabar Village, Loli District, West Sumba Regency. Data analysis techniques in this study were conducted during and after data collection. The results show that gravestones in Waitabar Village contain mathematical concepts such as blocks and cylinders that can be used in contextual mathematics learning in schools.